Diagnostic and therapeutic approach to obscure gastrointestinal bleeding in a patient with a jejunal gastrointestinal stromal tumor: a case report - Yuval, Jonathan B (BioMed Central, 2014)
BACKGROUND: Gastrointestinal stromal tumors of the alimentary tract may present with severe bleeding. Localization and treatment of obscure gastrointestinal bleeding is challenging in cases of negative bi-directional endoscopy. CASE PRESENTATION: A previously healthy 64-year-old Caucasian female presented with clinical signs of active gastrointestinal bleeding. Esophagogastroduodenoscopy was normal, and colonoscopy revealed passage of blood from the small bowel. Computerized tomography angiography demonstrated a hypervascular lesion with active extravasation located in the jejunum. Angiography of the superior mesenteric artery revealed a focal hypervascular mass in the jejunum, and super selective distal coil embolization of the feeding vessel was performed. When the patient was taken for laparoscopic exploration, a 2.5 cm tumor arising from the anti-mesenteric border of the proximal jejunum was identified and resected with primary anastomosis. Pathological results demonstrated a gastrointestinal stromal tumor with a low proliferation index of 1%. Small erosions in the adjacent mucosa confirmed the locus of bleeding. CONCLUSIONS: Computerized tomography is a useful tool for initial diagnosis of submucosal alimentary tumors in patients with obscure but clinically overt gastrointestinal bleeding. Selective angiography, following positive computerized tomography findings, is an important modality to allow both localization and hemostasis in actively bleeding small bowel tumors, but the procedure carries the risk of bowel necrosis. Complete surgical resection remains the mainstay for treatment of gastrointestinal stromal tumors.